Peningkatan Pembelajaran Menulis Karangan Persuasi Dengan Menerapkan Model Pembelajaran Berbasis Contoh - Ihramsari Akidah (Fakultas Sastra - Universitas Muslim Indonesia, 2018)
Writing as a productive activity for high school students can provide many benefits, such as developing creativity, instilling courage and self-confidence, organizing and clarifying thoughts, ways of thinking, intelligence, and emotional sensitivity of students. The many benefits can be obtained in learning to write, the writing activity should be one of the activities that students like. The researcher has an idea to conduct research with the title